Options for Designing a Green Investment Scheme for Bulgaria : Volume 2. Annexes - World Bank (Washington DC, 2013)
This report examines the various issues surround the Greening of Assigned Amount Units (AAUs) with a view to provide recommendations to the Government of Bulgaria and interested parties on considerations and approaches for a potential transaction involving a sale of AAUs and implementing a green investment scheme in Bulgaria. The study examines three options for a Green Investment Scheme (GIS) fund structure and reviews the implications for GIS implementation, inter-ministerial coordination, capital mobilization, risk mitigation and management and fiduciary obligations. The two suitable options for a GIS include the GIS designed as a governmental organization under Bulgarian public law, or where the GIS is designed as a special purpose corporation (a profit making entity under Bulgarian private law). In both options the GIS fund would need managerial capacity to administer one or several funds, in order to identify eligible projects and to supervise their implementation. The report also notes possible constraints for Bulgaria in setting up GIS along the recommended structure. These constraints could result from fiscal or macro considerations and an alternative approach is also suggested.